A comparison of reinforcing effectiveness and drug-seeking reinstatement of 2-fluorodeschloroketamine and ketamine in self-administered rats - Du, Han; Lai, Miaojun; Zhuang, Dingding; Fu, Dan; Zhou, Yiying; Chen, Shanshan; Wang, Fangmin; Xu, Zemin; Liu, Huifen; Wang, Youmei; Xu, Peng; Zhou, Wenhua (Frontiers in Molecular Neuroscience, 2022)
2-Fluorodeschloroketamine (2F-DCK), a structural analog of ketamine, has been reported to cause impaired consciousness, agitation and hallucinationmental symptoms in abuse cases. It has similar reinforcing and discriminative effects as ketamine. However, the reinforcing efficacy and drug-seeking reinstatement of this analog have not been clarified to date. In this study, the effectiveness of 2F-DCK and ketamine was compared using a behavioral economics demand curve. The reinstatement of 2F-DCK- and ketamine-seeking behaviors induced by either conditioned cues or self-priming was also analyzed. Rats were intravenously self-administered 2F-DCK and ketamine at a dose of 0.5 mg/kg/infusion under a reinforcing schedule of fixed ratio 1 (FR1) with 4 h of daily training for at least 10 consecutive days. The elasticity coefficient parameter α and the essential value of the demand curve in the two groups were similar. Both groups of rats showed significant drug-seeking behavior induced either by conditional cues or by 2F-DCK and ketamine priming. Moreover, the α parameter was inversely related to the degree of reinstatement induced by cues or drug priming in both groups. In total, the expression levels of brain-derived neurotrophic factor (BDNF) and phosphorylated cAMP response element-binding protein (p-CREB) in the nucleus accumbens in both extinguished and reinstated rats were significantly lower than those in the control. Total Akt, glycogen synthase kinase (GSK)-3β, mammalian target of rapamycin (mTOR), and extracellular signal-related kinase (ERK) expression also decreased, but p-Akt, p-GSK-3β, p-mTOR, and p-ERK levels increased in both extinguished and reinstated rats. This is the first study to demonstrate that 2F-DCK has similar reinforcing efficacy, effects, effectiveness, and post-withdrawal cravings as ketamine after repeated use. These data suggest that the downregulation of CREB/BDNF and upregulation of the Akt/mTOR/GSK-3β signaling pathway in the nucleus accumbens may be involved in ketamine or 2F-DCK relapse.